Peningkatan Pemahaman Bahaya Pergaulan Bebas Pada Kalangan Remaja Di SMA Pertiwi 1 Padang - Noffitri Yetti; Sisca Ramadhani; Reysa Yuliandarini; Yulia Hanoselina (CV. ITTC INDONESIA, 2025)
Nowadays, there are many cases related to juvenile delinquency in the community. With several factors that make teenagers vulnerable to being influenced by free association which results in various situations such as free sex and crime. Thus, Padang State University students conduct socialization to be able to provide understanding and reminders for students about the negative impacts of free association and help control their lives to be more vigilant. In the socialization at SMA Pertiwi 1 Padang, a face-to-face method was used, accompanied by questions and answers, sharing, and giving prizes to active students. The implementation of the socialization was carried out for one hour, involving 20 students of SMA Pertiwi 1 Padang. With the socialization they received, they were able to provide an understanding of the dangers of free association, negative impacts, and efforts to handle it. Consistency is needed from students so that they can always avoid free association.